Complete Genome Sequence of Bacillus subtilis Phage φ105 - Zeigler, Daniel R. (American Society for Microbiology, 2013)
A complete 39,318-bp genome sequence containing 52 coding sequences has been determined for the Bacillus subtilis temperate phage φ105. In a lysogen, B. subtilis strain 1L32, the φ105 prophage interrupts the radC locus, a part of the competence-induced ComK regulon.